The Physiological Mechanisms and Hurdles of Efficient Water–Nitrogen Utilization in Maize Production: A Review - Xichao Sun; Qian Zhao; Jia Gao; Zheng Liu (Plants, 2025)
Maize (Zea mays L.) is one of the most important staple food crops globally. One-third of global maize production is located in areas with high or extreme water scarcity and concurrently faces the challenge of low nitrogen use efficiency. Therefore, achieving synergistically high-efficiency water and nitrogen utilization in maize production is of great significance for agricultural sustainable development and global food security. In recent years, more articles have focused on the physiological mechanisms and management practices of efficient water and nitrogen utilization in maize. Unfortunately, there is a relative scarcity of research on the interactive effects between water and nitrogen on the development of young ears, which plays a crucial role in maize productivity. By compiling the most pertinent publications, this review endeavors to consolidate the existing knowledge on the interactive effects between water and nitrogen on maize production. Moreover, it advances potential physiological mechanisms and strategies for high-efficiency water and nitrogen utilization in terms of root system functioning, phytohormones, metabolism, and organ development. The changes in the availability of water and nitrogen have a significant impact on the development of young ears during the critical period, which in turn directly determines the grain number per ear and grain weight.